BACTERIAL CONTAMINATION OF STETHOSCOPES - Bukharie, Huda A. (Medknow Publications & Media Pvt Ltd, 2004)
BACKGROUND: A stethoscope, an essential tool of the medical profession, can become a source of nosocomial infection. OBJECTIVE: To determine the frequency of bacterial contamination of stethoscopes as well as the practices used for cleaning them. METHODS: Cultures were taken from 100 stethoscopes used by different medical personnel in different hospital services. The stethoscopes were collected while the staff filled in a questionnaire. RESULTS: Thirty (30%) out of the 100 stethoscopes surveyed were contaminated with microorganisms. The majority of organisms isolated were gram-positive bacteria (gram positive bacilli 12%, gram-negative bacteria 9%, gram-positive cocci 9%). None of the stethoscopes grew methicillin-resistant staphylococcus aureus. Overall, 21% of the health personnel cleaned their stethoscopes daily, 47% weekly, and 32% yearly. None of the health care workers cleaned their stethoscopes after every patient. Nurses cleaned their stethoscopes more often than physicians and medical students. CONCLUSION: Stethoscopes may be important in the spread of infectious agents. Their regular disinfection after use on each patient should be considered, particularly in such areas of the hospital, as the critical care units, and oncology units which house many patients with antibiotic-resistant organisms.